2019
DOI: 10.17557/tjfc.643524
|View full text |Cite
|
Sign up to set email alerts
|

Forage Yield and Protein Content of Different Field Pea Cultivars and Oat Mixtures Grown as Winter Crops

Abstract: Monoculture and intensive use of mechanization and inorganic chemicals are leading to degradation and erosion of our soils and agro-ecosystems. At the same time, the production of animal feeds that are rich in protein is constantly decreasing in many European countries. Modest cultivation needs, favorable content of nutrients, and beneficial effect on the environment, make field pea and oat mixtures promising crops to tackle these issues. In three growing seasons and without irrigation or fertilisation, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Among the treatments, the application with the highest herbage yield was found in pure oat application with 578.89 kg da -1 , while 75% common vetch + 25% annual ryegrass had the highest value among the mixtures (Appendix A,B). Kocer and Albayrak [22] reported that in a mixture trial with forage pea, oat and barley, oat had the highest yield in terms of herbage yield and in mixtures, forage pea -oat mixtures had high values.…”
Section: Resultsmentioning
confidence: 99%
“…Among the treatments, the application with the highest herbage yield was found in pure oat application with 578.89 kg da -1 , while 75% common vetch + 25% annual ryegrass had the highest value among the mixtures (Appendix A,B). Kocer and Albayrak [22] reported that in a mixture trial with forage pea, oat and barley, oat had the highest yield in terms of herbage yield and in mixtures, forage pea -oat mixtures had high values.…”
Section: Resultsmentioning
confidence: 99%
“…Największy plon świeżej masy (47,0 t ha -1 ) zebrano z mieszanki grochu siewnego z pszenżytem jarym o udziale komponentów 50% + 50%. Zdaniem Tuna i Orak [2007] oraz Krga i in. [2019Krga i in.…”
Section: Wyniki I Dyskusjaunclassified
“…Pea ( Pisum sativum L.) is a multifunctional species used for human consumption worldwide, and it is mainly cultivated in Western Europe, North America, India, Australia, Pakistan, and South America (Das et al., 2019; Devi et al., 2021; Kocer & Albayrak, 2012; Ma et al., 2017; Saxesena et al., 2013). This legume contributes to meeting the global dietary needs of more than 900 million people in vulnerable condition (Ceyhan & Avci, 2005; Das et al., 2019; Devi et al., 2019).…”
Section: Introductionmentioning
confidence: 99%